Quantitative immunology of immune hemolytic anemia: II. The relationship of cell-bound antibody to hemolysis and the effect of treatment - Rosse, Wendell F. (1971)
The concentration of cell-bound and serum antibody was determined in a series of patients with warm antibody immune hemolytic anemia by determining the amount of C[unk]1 fixed to the cells by anti-IgG. This was compared to the rate of hemolysis as determined by hemoglobin concentration and reticulocyte count, or the endogenous production of carbon monoxide. The rate of hemolysis was, in general, proportional to the concentration of cell-bound antibody. In splenectomized patients, the rate of hemolysis was very much less than in unsplenectomized patients for a given concentration of cell-bound antibody. When prednisone was given, three effects were noted: (a) at high doses of drug, the concentration of cell-bound antibody decreased rapidly and the concentration of serum antibody increased, suggesting that the affinity of antibody for antigen had been altered; (b) in patients achieving remission, the concentration of serum antibody fell to low levels but rose again if the dose of prednisone was insufficient; (c) in one patient, prednisone appeared to inhibit sequestration of highly sensitized cells.